Congenital and childhood plexiform (Multinodular) cellular Schwannoma - A troublesome mimic of malignant peripheral nerve sheath tumor - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
We present six cases of a plexiforrn nerve sheath tumor of childhood that previously had been designated a form of malignant peripheral nerve sheath tumor (MPNST), and we provide evidence that such tumors are in fact benign plexiform cellular schwannomas. At presentation, the four girls and two boys ranged in age from 2 to 15 months with tumors of the leg (four), deep groin and upper thigh (one), and pelvis (one). Of the six lesions, five were congenital and none was associated with type 1 neurofibromatosis. Tumor sizes ranged from 2.0 to 9 cm, with three larger than 5 cm. Three tumors were well circumscribed, two were purely infiltrative, and one had a mixed circumscribed and infiltrative growth pattern. Peripheral nerve involvement was evident in two cases. Grossly, the tumors were multinodular or plexiform in configuration and, on sectioning, lobulated and homogeneously tan without necrosis. Characteristic histologic features included hypercellularity, composition of cells spindle in shape with elongate hyperchromatic nuclei, and indistinct cellular outlines. Their nuclei varied minimally in size and shape but were at least three times the size of typical neurofibroma nuclei. Mitoses were seen in every tumor and in the areas of greatest proliferative activity ranged from 4 to 31/10 high power fields. MIB-1 staining of at least 30% of the cells was noted in three cases. In five cases in which p53 immunoreactions were performed, no nuclear staining was evident. That the tumors are schwannomas was evident from their uniform strong staining for S-100 protein and an ultrastructure in all five cases showing only differentiated neoplastic Schwann cells. Architecturally, the tumors differed from conventional schwannoma and nonplexiform cellular schwannomas by their lack of both well-formed capsules and degenerative changes. Follow-up was available in all cases and ranged from 2 to 13.6 years. All tumors recurred locally and were treated by local resections. With the exception of one child lost to follow-up at 25 months, all the children are alive and free of disease. Our data combined with cases previously reported by Meis-Kindblom and Enzinger show a childhood peripheral nerve tumor unassociated with type 1 neurofibromatosis, occurring most commonly in infants, often presenting as a congenital tumor and, though prone to local recurrence, having no metastatic potential. The behavior is that of a benign tumor, although its often rapid growth, hypercellularity and increased mitotic activity, sometimes locally aggressive behavior, and difficulties encountered in obtaining tumor-free margins are unsettling to pathologist and clinician alike. These features may lead to a misdiagnosis of malignancy, which could result in harmful overtreatment.
Keywords: plexiform peripheral nerve tumor; congenital peripheral nerve tumor; plexiform schwannoma; cellular schwannoma